Coexistence of grasses and shrubs in Patagonian steppes. Norm or exception? - Biancari, Lucio (2023)
Community ecology’s central challenge is to define and corroborate theoretical frameworks that predict -at least in general terms- the composition of communities. The predictive power of a theory based on interspecific interactions and ecological niches has been questioned (Lawton 1999; Hubbell 2001; Ricklefs 2008; but see Brooker &Callaway 2009). These authors also propose that part of the problem is that the composition of a given community, and therefore its species richness and diversity, iscontingent on different and varied local factors. Therefore, expanding the spatial scale to the regional level averages these “local” contingencies and increases the predictive power (Lawton 1999). Accordingly, it has been proposed that the global diagram of biomes distribution in relation to the main climate descriptors (i.e. average annual temperature and precipitation, MAT and MAP respectively) is a solid start for community ecology (Keddy 1994; Lawton 1999). But semiarid environments put a note of warning to this research program. It is notorious that within the range of -5 to 20 °C of MAT and from 150 to 1200 mm of MAP, the biomes are not unequivocally defined as it happens in the rest of the climates (Whittaker 1972). In this climatic envelope, grasslands, shrubby steppes, savannas, and spiny forests overlap their distribution ranges. In other words, there is uncertainty in predicting the basic community composition of life-forms. This vagueness syndrome in the proportion of woody and grass species has been named “the savanna problem” (Sarmiento 1984; Vazquez et al. 2010) to indicate the conundrum that two very different life-forms can coexist in anample range of ecological conditions (House et al. 2003). The existence of mixed communities such as savannas or grass-shrub steppes under semiarid climates has been the subject of several theories, empirical studies, and discussions. In general, the initial assumption was that the ecological differences in the water economy of woody and herbaceous species were large enough to work with avery simplified community model in which two types of plants interact -compete- (Walter 1971). Early models also included stress and disturbance regimes. Thus, grazing intensification in conjunction with very dry periods can change the relative abundance of woody and herbaceous species precluding coexistence (Walker et al. 1981). In this second type of models -competition plus grazing and extreme drought events-, the assumption was that these two life-forms also differed in their response to grazing (Eldridge et al. 2011; Venter et al. 2018). More recently, hypotheses about the existence of savannas have become more complex in terms of processes but also in spatial scales. They included different population responses among species within the same life-form ( Cipriotti & Aguiar 2010; Cipriotti et al. 2019) or patch dynamics (Meyer et al. 2009). Currently, the causes of coexistence and the great variability of relative coverage in mixed systems remain relevant but difficult to generalize (Jeltsch et al. 2000; House et al. 2003; Sankaran et al. 2004; Vazquez et al. 2010; Stevens et al. 2017; Venter et al. 2018). At the same time, it is necessary tocontinue collecting empirical data on the cover of woody and grass components over large geographical regions -sampling different environments and grazing management